Designing a Conceptual Model of Organizational Health and Its Relationship with Health Literacy of Lower Secondary School Teachers in Tehran - Alaei, Fatemeh; Fathi Vernosfaderani, Leila; Ahghar, Ghodsi (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study was conducted with the aim of designing a conceptual model of organizational health and its relationship with the health literacy of lower secondary school teachers in Tehran. Methods and Materials: This study employed a mixed-method (qualitative-quantitative) exploratory sequential design. The statistical population included all lower secondary school teachers in Tehran in 2022, with 20 participants selected through theoretical saturation for the qualitative phase and 300 participants selected through multistage sampling for the quantitative phase. Data collection involved semi-structured interviews, a researcher-made questionnaire on organizational health, and a standardized health literacy questionnaire by Andreade et al. (2017). Data analysis was conducted using thematic analysis, Pearson correlation, confirmatory and exploratory factor analysis, and one-sample t-test with SPSS-v21 and Lisrel-v8 software. Findings: The results identified eight main dimensions from 78 indicators: organizational (commitment, support, health culture), individual (individual characteristics, interpersonal characteristics, work-life balance), and environmental (environmental dynamics, environmental outlook). The conceptual model demonstrated that organizational health significantly impacts teachers’ health literacy, with model fit indices (GFI = 0.99, AGFI = 0.96, CFI = 0.99, RMSEA = 0.071) indicating an excellent fit. Conclusion: The study concluded that organizational health plays a crucial role in enhancing teachers’ health literacy. Promoting a health-oriented culture, fostering supportive environments, and addressing individual and environmental factors are essential for improving teachers’ well-being and professional effectiveness.